PENGELOLAAN BUMDES HIMPUNAN PENDUDUK PEMAKAI AIR MINUM (HIPPAM) DALAM PEMBERDAYAAN EKONOMI DESA PERSPEKTIF EKONOMI ISLAM - Habibati, Petty Nur; Rohman , Abdur (Ulumuna: Jurnal Studi Keilsman, 2022)
Village Owned Enterprises (BUMDes) Primatera in managing HIPPAM in Prigi Village, Kanor District, Bojonegoro Regency so that HIPPAM BUMDes becomes a business entity and village economic empowerment program. The purpose of this study was to find out about the management of BUMDes HIPPAM in Prigi Kanor Bojonegoro Village, to find out village economic empowerment from an Islamic economic perspective. The method used in this study uses a descriptive qualitative approach, the source of data obtained from primary and secondary data. Data was collected using observation data collection techniques, interviews and documentation. The technical analysis of this research data includes data reduction, data presentation and conclusion/verification. The results of this study show that the management of BUMDes in Prigi village has been well carried out in accordance with the purpose of BUMDes, but the BUMDes of HIPPAM business unit has not been evenly distributed due to lack of capital and network. The empowerment of SOEs for the HIPPAM business unit, the indicators of Tinkin Maddi (Material) of the community experienced changes in expenditure to get water sources, with the presence of HIPPAM being more affordable. Ma'nawi's indicators (non-materially) with HIPPAM make it easier for people to get clean water/drinking water, reduce accidents, make it easier for people to get water to be used by wudhu in the event of a power outage, transparent and accountable financial reporting, socialization of the importance of clean water to the waterfor everyday life and provide a method of Clarification. Keywords: Management, BUMDes, Community Empowerment, Islamic Economics